2019
DOI: 10.1590/fst.36617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion cooking on physicochemical properties of tuna meat-based extrudates

Abstract: Effect of extrusion cooking using different corn starch contents on the physicochemical properties (expansion ratio, bulk density, color, hardness, protein in vitro digestibility, crude protein content, thermal properties and microstructure) of tuna meat-based extrudates was investigated. The results showed that the increased corn starch content led to darker, greener, yellower and lower crude protein content of extrudates, but no significant difference was observed in expansion ratio, bulk density and hardnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The results are slightly below the range (2.941 to 3.559) reported by Naseer et al (2021), for extrudate almond-pearl millet (APM) based snack but close to the trends (2.42 to 3.30) reported by Sahu and Patel (2020) for RTE extruded products and 2.0 to 2.6 reported by Omwamba and Mahungu (2014) for proteinrich ready-to-eat extruded snack from a composite blend of rice, sorghum, and soybean flour. In addition, the results confirm well the values (1.17±0.04 to 1.23±0.07) reported by Fang et al (2019) for tuna meat-based extrudates. The sectional expansion ratio varied from 0.88-1.56 and falls within the range of 1.07 to 3.76 (mm 2 sectional area of the extrudate to sectional area of die), reported by Rweyemamu et al (2015).…”
Section: Expansion Ratio and Bulk Density Of Ready-to-eat Baby Foodssupporting
confidence: 91%
“…The results are slightly below the range (2.941 to 3.559) reported by Naseer et al (2021), for extrudate almond-pearl millet (APM) based snack but close to the trends (2.42 to 3.30) reported by Sahu and Patel (2020) for RTE extruded products and 2.0 to 2.6 reported by Omwamba and Mahungu (2014) for proteinrich ready-to-eat extruded snack from a composite blend of rice, sorghum, and soybean flour. In addition, the results confirm well the values (1.17±0.04 to 1.23±0.07) reported by Fang et al (2019) for tuna meat-based extrudates. The sectional expansion ratio varied from 0.88-1.56 and falls within the range of 1.07 to 3.76 (mm 2 sectional area of the extrudate to sectional area of die), reported by Rweyemamu et al (2015).…”
Section: Expansion Ratio and Bulk Density Of Ready-to-eat Baby Foodssupporting
confidence: 91%
“…Interestingly, there was no discernible distinction ( p > 0.05) in cooking yield observed between the meat nuggets prepared with 1.5% and 3.0% MPP. In a previous study, Fang et al 72 indicated that the use of sugarcane fibre in chicken sausage formulation resulted in increased cooking yield and reduced water and fat loss. It is well established that use of dietary fibres in emulsion-based meat, as well as non-meat components, increases the cooking yield and decreases the water loss during cooking.…”
Section: Resultsmentioning
confidence: 99%